Integrating Dimensional and Discrete Theories of Emotions: A New Set of Anger- and Fear-Eliciting Stimuli for Children. Issue 5 (3rd September 2017) - Scaini, Simona; Rancoita, Paola M. V.; Martoni, Riccardo M.; Omero, Micol; Ogliari, Anna; Brombin, Chiara
ABSTRACT: The selection of appropriate stimuli for inducing specific emotional states has become one of the most challenging topics in psychological research. In the literature there is a lack of affective picture database specifically suited to investigate emotional response in children. Here the authors present the methodology that led us to create a new database (called Anger- and Fear-Eliciting Stimuli for Children) of affective stimuli inducing experiences of 3 target emotions (neutral, anger, and fear) to use in experimental session involving children. A total of 84 children were asked to (a) indicate the perceived emotion and its intensity and (b) rate the three affective dimensions of the Self-Assessment Manikin (SAM). Based on concordance between labeled and expected target emotion, the authors decided to select 15 stimuli to be included in Multivariate modeling techniques were applied to evaluate the association between expected target emotion and SAM ratings. The authors found that the hit rate for the neutral pictures was good (greater than 81%), for fear-eliciting pictures it was greater than 64%, and for anger-eliciting pictures it was moderate (between 45% and 56%). The study results reveal also an age effect only in the arousal scale. However, the authors did not find significant gender-related differences in SAM ratings.